The Influence of Current Ratio (CR), Return On Investment (ROI), Debt To Equity Ratio (DER) on Company Value with Good Corporate Governance as a Moderating Variable (Case Study of Manufacturing Companies Listed on the Indonesian Stock Exchange for the 2016-2020 Period): (Case Study of Manufacturing Companies Listed on the Indonesian Stock Exchange for the 2016-2020 Period) - Meliyanti; Pahlevi, Cepi; Rahim, Fauzi R (Jurnal Penelitian Ekonomi Dan Akuntansi, 2024)
This study investigates the impact of strong corporate governance on the relationship between current ratio (CR), return on investment (ROI), and debt to equity ratio (DER) and company value. This study investigates manufacturing companies that were publicly traded on the Indonesia Stock Exchange from 2016 to 2020. This study investigates hypotheses with a quantitative methodology. The sample included nine issuers. Utilising electronic research tools and adhering to library research guidelines are essential elements of the data collecting process. Regression moderation analysis, classical assumption testing, and descriptive statistical analysis are all techniques used in the process of analysing data. Evidence suggests that the current ratio (CR) of a company has little impact on its total worth. The value of a corporation is directly impacted by the Return on Investment (ROI). The debt to equity ratio (DER) has no impact on the worth of a firm. Efficient corporate governance has the ability to reduce the relationship between a company's value and its current ratio (CR). Efficient corporate governance may manage the relationship between return on investment (ROI) and the firm's value. Effective corporate governance may impact the relationship between a company's value and its debt-to-equity ratio (DER). Keywords: Current Ratio (CR), Return On Investment (ROI), Debt To Equity Ratio (DER), Company Value, Good Corporate Governance.